Analisis Pengaruh Suhu Dan Partial Shading Terhadap Output Daya PV 100-WP Untuk Sistem Hidroponik - Saputra, Masramdhani; Santoso, Asfari Hariz; Gumilang, Binar Surya; Pratama, Tio Chandra Ardhi (Politeknik Negeri Malang, 2023)
This experiment discusses the effect of the variability of solar radiation due to partial shading and surface temperature of the PV Panel on the output power of 100 Wp solar panels. This study begins by determining the load of the system, i.e. DC pump in the nutrient circulation system of the DFT hydroponic system. From there, we can observe the change in solar panel power output and PV surface temperature change due to partial shade. This survey method actually measures the temperature and intensity of solar radiation and measures the power output of a solar panel, and the tools used are thermal sensors used to measure the surface temperature of solar panels. Solar power meter. to measure the solar irradiance and use the multimeter to measure the voltage and current, 10A capacity SCC battery, 100Wp capacity solar panel and 65Ah battery. The test will be conducted for 5 days, starting from 09:00 to 15:00 every day. This result shows that temperature increase affects the output power decrease when the solar panel is in normal condition (not half shaded condition). On the other hand, when partial shade conditions increase, the temperature does not affect the decrease in solar panel output power. The greater the intensity of partial shade produced by the solar panel, the lower the output power. However, for short periods of partial shade, the output power produced tends to be more stable than under normal conditions.